Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. Extreme southern terminal of mts. [mountains] which form east side of Kjerulfs [Kjerulf] Fjord. Photo taken looking overhead to the north. This photo is No. 27 in pan C.